2021
DOI: 10.1155/2021/9970627
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Inflammation and Redox Imbalance in Umbilical Cord in Pregnancies with and without Preeclampsia and Consequent Perinatal Outcomes

Abstract: Objective. To compare redox imbalance and inflammation biomarkers in umbilical cords from pregnancies with and without preeclampsia (PE) and to analyse their relationships with perinatal outcomes. Methods. A controlled cross-sectional study was conducted in Maceió, Alagoas, Brazil, that involved pregnant women with PE and a group of women without the disease, through the application of a standardized questionnaire. After delivery, umbilical cord samples were collected to measure antioxidant defense, products f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 74 publications
(102 reference statements)
0
6
0
Order By: Relevance
“…Moreover, oxidate stress, which was characterized by lipid peroxidation accumulation, also plays a crucial role in the pathogenesis of PE. Recently, Fragoso et al reported that the umbilical cords from PE pregnancies showed higher levels of antioxidants including glutathione peroxidase (GPx) and malondialdehyde (MDA) than pregnancies without PE diagnosis, indicating the defensive mechanism to maintain the oxidative balance ( Fragoso et al, 2021 ). Despite all these efforts, the mechanisms regulating the onset and progression of PE remain largely unknown, making it crucial to explore highly sensitive biomarkers to provide an early and intensive care for patients at risk ( Grill et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, oxidate stress, which was characterized by lipid peroxidation accumulation, also plays a crucial role in the pathogenesis of PE. Recently, Fragoso et al reported that the umbilical cords from PE pregnancies showed higher levels of antioxidants including glutathione peroxidase (GPx) and malondialdehyde (MDA) than pregnancies without PE diagnosis, indicating the defensive mechanism to maintain the oxidative balance ( Fragoso et al, 2021 ). Despite all these efforts, the mechanisms regulating the onset and progression of PE remain largely unknown, making it crucial to explore highly sensitive biomarkers to provide an early and intensive care for patients at risk ( Grill et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, identifying, understanding, and quantifying the contribution of pre-and postnatal processes to endothelial dysfunction is challenging and requires an early endothelial evaluation to limit confounding factors (103). Although many fetal processes are not fully understood, the available endothelial biomarkers to perform this evaluation in NICU are numerous (76,103,152,175,260). They await further studies to validate their diagnostic and therapeutic potential.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies investigated, through cord blood samples analysis, the oxidant and antioxidant state of newborns of preeclamptic women, with or without FGR, compared to newborns from physiological pregnancies (156,(174)(175)(176)(177)(178)(179)(180)(181)(182)(183). Different analytical methods and some biomarkers have been used to measure oxidative stress, such as direct detection of ROS (e.g., hydrogen peroxide, H 2 O 2 ), indirect research of the peroxidation products of lipids and proteins (e.g., malondialdehyde and protein carbonyl levels), and activity evaluation of antioxidant enzymes (e.g., glutathione peroxidase).…”
Section: Perinatal Evidence and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…During this time, vascular resistance decreases, and the diameter of placental vessels increases. This provides blood perfusion and protects the fetus against hypoxemia, and during delivery, against reduced uteroplacental blood flow [14,15].…”
Section: Introduction 1oxidative Stress During Pregnancy and Childbirthmentioning
confidence: 99%